The role of potassium and host calcium signaling in Toxoplasma gondii egress. (March 2021) - Vella, Stephen A.; Moore, Christina A.; Li, Zhu-Hong; Hortua Triana, Miryam A.; Potapenko, Evgeniy; Moreno, Silvia N.J.
Graphical abstract: Highlights: Toxoplasma gondii replicates inside host cells and takes up Ca2+ from the host cytosol. T. gondii uses extracellular Ca2+ which contributes to reach a threshold needed for egress. Two peaks of Ca2+ precede parasite egress. Intracellular and extracellular stores contribute. It is possible to patch infected cells to deliver defined Ca2+ concentrations to trigger egress. Reduction of the surrounding potassium concentration modulates the rate of egress. Abstract: Toxoplasma gondii is an obligate intracellular parasite and replicates inside a parasitophorous vacuole (PV) within the host cell. The membrane of the PV (PVM) contains pores that permits for equilibration of ions and small molecules between the host cytosol and the PV lumen. Ca 2+ signaling is universal and both T. gondii and its mammalian host cell utilize Ca 2+ signals to stimulate diverse cellular functions. Egress of T. gondii from host cells is an essential step for the infection cycle of T. gondii, and a cytosolic Ca 2+ increase initiates a Ca 2+ signaling cascade that culminates in the stimulation of motility and egress. In this work we demonstrate that intracellular T. gondii tachyzoites are able to take up Ca 2+ from the host cytoplasm during host cell signaling events. Both intracellular and extracellular Ca 2+ sources are important in reaching a threshold of parasite cytosolic Ca 2+ needed for successful egress. Two peaks of Ca 2+ were observed in egressing single parasites with the second peak resulting from Ca 2+ entry. We patched infected host cells to allow the delivery of precise concentrations of Ca 2+ for the stimulation of motility and egress. Using this approach of patching infected host cells, allowed us to determine that increasing the host cytosolic Ca 2+ to a specific concentration can trigger egress, which is further accelerated by diminishing the concentration of potassium (K + ).